Do ban-the-box policies increase the hiring of applicants with criminal records? - Deborah M. Weiss; William Dawson; Ronald McKinley; Lee Webster (PLoS ONE, 2025)
Many United States jurisdictions have enacted Ban-the-Box (BTB) laws that are intended to improve the employment prospects of individuals with criminal records. The best-known feature of BTB statutes is a “screening ban:” employers cannot inquire about a criminal record until they have made a conditional offer of employment. Many BTB statutes contain a less well-known “use prohibition:” employers cannot withdraw a conditional offer based on a criminal record unless that record is sufficiently related to fulfillment of potential job duties. In this paper we provide the first evidence of the association of BTB policies with variation in the progression of candidates through hiring phases after the screening process. We use unique applicant-level data obtained from an employer before and after it voluntarily implemented a BTB policy. We find that the enactment of the BTB policy has little or no association with the rate at which individuals with criminal records survive the candidate assessment process and receive conditional employment offers. Indeed, our findings suggest a modest indication of a negative association between the implementation of BTB policies and the hiring of individuals with prior convictions for specific offenses. The observed pattern could be explained if, after losing access to criminal history, employers increase their reliance on hiring criteria that are correlated to criminal history. We also find that the rate at which individuals with a criminal record survive a final background check does not change after the implementation of the joint BTB policies. We find weak evidence that implementation of the two BTB policies is associated with worse outcomes for individuals with records of more serious offenses.